The Tudors. The final season [videorecording (DVD)] - Hirst, Michael, 1952- (DVD video., 2010)
The Tudors dramatize the tumultuous years of King Henry VIII's nearly 40 year, omnipotent reign (1509-1547). The final season follows the latter years of one of the greatest figures of Engilish history, King Henry the 8th and his marriages to his fifth wife, Catharine Howard, and his sixth wife Catharine Parr.